H2O‐Boosted MgProton Collaborated Energy Storage for Rechargeable Mg‐Metal Batteries. Issue 34 (14th July 2022) - Yang, Chaoran; Pu, Zhichen; Jiang, Zhenfei; Gao, Xiaowen; Wang, Kewei; Wang, Shiyang; Chai, Yuming; Li, Qi; Wu, Xuejun; Xiao, Yunlong; Xu, Dongsheng
Abstract: Rechargeable magnesium batteries (RMBs) are a kind of energy storage system with high safety, low cost, and high volumetric energy density. In general perception, H2 O will passivate the Mg‐metal anode. But herein, a coordination–hydrolysis strategy is developed, in which H2 O can be used as an additive to produce dissociated H + . Moreover, MgH + energy storage mechanism is discovered on CuSe cathode, which helps the specific capacity and energy density enhance to 480 mAh g −1 and 413 Wh kg −1, respectively. This coordination–hydrolysis strategy also promotes the conductivity and electron transfer ability of electrolyte. Consequently, the specific capacity can remain 247 mAh g −1 even at 2 A g −1 . MgH + energy storage route gets rid of massive cathode material, and protons have the smallest size and lightest weight, whose theoretical energy density can reach 4230 Wh kg −1 . The results elucidated here provide a new route for energy‐dense RMBs. Abstract : Through a coordination–hydrolysis strategy, not only the conventional problem of passivation of magnesium metal by water is overcome, but also the addition of water can improve the deposition/dissolution performance and ion transport rate of Mg 2+ . A hydrolytic reaction produces free protons, which can participate in the reversible redox reaction, providing a huge performance improvement for the battery.